[Tibor Höffler 3.]
1931-1951: weekend in the Népliget, excerpts from a Chaplin film, springtime in the garden, speed race, vacation in Sikonda, Simontornya and Balatonalmádi, excursion to the Mecsek mountains, soldiers starting up the front-line, vacation in Harkány